The alteration of first trimester screening markers in fresh and frozen-thawed blastocyst transfers - Dokuzeylül Güngör, Nur; Gürbüz, Tuğba; Gökmen Karasu, Ayşe Filiz; Erşahin, Aynur (The European Research Journal, 2019)
Objective: The aim of this study was to investigate whether first trimester combined screening for major fetal trisomies is influenced by assisted reproduction techniques (ART) from blastocyst transfer, with or without cryopreservation. Methods: This study is a retrospective analysis involving 115 singleton pregnancies with euploid fetuses recruited between January 2017 and December 2017. Sixty-five women conceived with fresh blastocysts from in vitro fertilization (IVF) cycles (fresh-blasto), 50 with frozen-thawed blastocysts. All cases underwent ultrasound assessment at 11+0 - 13+6 weeks with measurements of crown rump length, nuchal translucency (NT) , free beta-human chorionic gonadotrophin (free β-hCG) and pregnancy-associated plasma protein A (PAPP-A) concentrations. Results: Baseline characteristics and pregnancy outcomes did not differ substantially among the study groups. The NT was not significantly different in the frozen-thawed -blasto compared to the fresh-blasto group (p = 0.741). The free β-hCG levels was not significantly different in frozen-thawed-blasto group compared to fresh-blasto group (p = 0.495). The two groups showed no significant difference in the PAPP-A levels (p = 0.139). The median delta crown rump length was also not significantly different among the two groups (p = 0.758). Conclusions: In ART pregnancies from blastocyst transfer, with or without cryopreservation, the NT measurement, free β-hCG concentration and PAPP-A levels did not show any significant difference. These features are apparently unrelated to the outcome of pregnancy and may be due to alterations or delays in embryogenesis or placentation with potential relevance for the screening test performance.